High photoresponsivity in ultrathin 2D lateral graphene:WS2:graphene photodetectors using direct CVD growth - Chen, T; Sheng, Y; Zhou, Y; Chang, R-J; Wang, X; Huang, H; Zhang, Q; Hou, L; Warner, JH (American Chemical Society, 2019)
We show that reducing the degree of van der Waals overlapping in all 2D ultrathin lateral devices composed of graphene:WS2:graphene leads to significant increase in photodetector responsivity. This is achieved by directly growing WS2 using chemical vapor deposition (CVD) in prepatterned graphene gaps to create epitaxial interfaces. Direct-CVD-grown graphene:WS2:graphene lateral photodetecting transistors exhibit high photoresponsivities reaching 121 A/W under 2.7 × 105 mW/cm2 532 nm illumination, which is around 2 orders of magnitude higher than similar devices made by the layer-by-layer transfer method. The photoresponsivity of our direct-CVD-grown device shows negative correlation with illumination power under different gate voltages, which is different from similar devices made by the transfer method. We show that the high photoresponsivity is due to the lowering of effective Schottky barrier height by improving the contact between graphene and WS2. Furthermore, the direct CVD growth reduces overlapping sections of WS2:Gr and leads to more uniform lateral systems. This approach provides insights into scalable manufacturing of high-quality 2D lateral electronic and optoelectronic devices.